Facets of Self in Schizophrenia: The Reliability and Accuracy of Trait Self-Knowledge. (July 2013) - Klein, Stanley B.; Altinyazar, Vesile; Metz, Molly A.
Disturbance of self is a core feature of schizophrenia. In this article, we argue that a nuanced appreciation of self is necessary to understand the relation between the self and its disruption. After discussing evidence for the fractionation of self into several functionally independent yet normally interacting systems of knowledge, we focus on a specific self-system: trait self-knowledge. This system has proven robust in the presence of a host of cognitive and neural impairments rendering other systems of self dysfunctional. Little, however, is known about how this system is affected by schizophrenia. Our findings indicate that, in accord with previous investigations demonstrating the resilience of trait self-knowledge, schizophrenic patients maintain both highly reliable and moderately accurate trait self-knowledge.